3D-QSAR studies of checkpoint kinase 1 inhibitors based on molecular docking and CoMFA - Wang, R.; Zhou, L.; Zuo, Zhili; Ma, X.; Yang, M. (Taylor & Francis Ltd, 2010)
Three-dimensional quantitative structure–activity relationship (3D-QSAR) studies were performed on a series of substituted 1,4-dihydroindeno[1,2-c]pyrazoles inhibitors, using molecular docking and comparative molecular field analysis (CoMFA). The docking results from GOLD 3.0.1 provide a reliable conformational alignment scheme for the 3D-QSAR model. Based on the docking conformations and alignments, highly predictive CoMFA model was built with cross-validated q 2 value of 0.534 and non-cross-validated partial least-squares analysis with the optimum components of six showed a conventional r 2 value of 0.911. The predictive ability of this model was validated by the testing set with a conventional r 2 value of 0.812. Based on the docking and CoMFA, we have identified some key features of the 1,4-dihydroindeno[1,2-c]pyrazoles derivatives that are responsible for checkpoint kinase 1 inhibitory activity. The analyses may be used to design more potent 1,4-dihydroindeno[1,2-c]pyrazoles derivatives and predict their activity prior to synthesis.